Chaucer - a medieval writer? - Martina Ožbolt (Acta Neophilologica, 1993)
For literary historians with only few exceptions (e.g . J.W. Mackail, W.P. Ker, A.C. Spearing) Geoffrey Chaucer is unquestionably and exclusively a medieval poet. The belief that his literaryproduction undoubtedly makes part of medieval English literature seems firmly established and any doubt about it futile. In spite ofthis aprioristic attitude towards the problem of the relationship between Chaucer and the Middle Ages there are at least two major elements which may make one doubt how correct it is to take Chaucer's medievalism for grante.